Research on effects of race of models and product involvement on consumer perceptions of local fashion advertisements. - Chan, Cindy Wai Teng. (2008)
The objective of this experimental study is to investigate the influence of models' race and product involvement in fashion print magazine advertisements, on consumers' attitudes toward advertisement and product, as well as purchase intention.